1986
DOI: 10.1111/j.1365-2621.1986.tb11110.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Dose Irradiation of Pork Loins on the Microflora, Sensory Characteristics and Fat Stability

Abstract: The effects of low dose (100 krad) irradiation on microflora, sensory characteristics, and development of oxidative rancidity of vacuum packaged pork loins was investigated after irradiation and during low temperature (4°C) storage up to 2 1 days. Irradiation reduced numbers of mesophiles, psychrotrophs, anaerobic bacteria (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 5 publications
(2 reference statements)
4
30
0
1
Order By: Relevance
“…Mattison et al (1986) showed that differences in sensory evaluation by triangle test were detected between irradiated and unirradiated pork loins 2 days after irradiation, but no difference was detected when the meat was sampled 7 days after irradiation. They hypothesized that some short-term effect may be responsible for this early difference in quality, but that this difference was time dependent.…”
Section: Discussionmentioning
confidence: 92%
“…Mattison et al (1986) showed that differences in sensory evaluation by triangle test were detected between irradiated and unirradiated pork loins 2 days after irradiation, but no difference was detected when the meat was sampled 7 days after irradiation. They hypothesized that some short-term effect may be responsible for this early difference in quality, but that this difference was time dependent.…”
Section: Discussionmentioning
confidence: 92%
“…Irradiation of fatty foods is known to produce free radicals which, in the presence of 02, can initiate autoxidation chain reactions which lead to rancidity (Nawar, 1983). Chipault & Mizuno (1966) showed that storage of irradiated ground beef or pork in the presence of O2 resulted in autoxidation and rancidity.…”
Section: Discussionmentioning
confidence: 99%
“…The TBARS values significantly increased (p b 0.05) after longer exposure to APP jets (0.5-20 min). Mattison et al (1986) reported that the acid patch can sense when the TBA values of fresh meat were more than 1.0 mg MA/kg. Although the TBARS values gradually increased with longer exposure to APP jets, the TBARS values in these studies were below 1.0 mg MA/kg.…”
Section: Effects Of App Jet Treatment On the Physicochemical Propertiesmentioning
confidence: 98%